Prognostic value of laboratory markers and clinical scores for mortality in intensive care unit patients with sepsis - So-yun Kim; Dukki Kim; Hyekyeong Ju; Song I. Lee (PLoS ONE, 2025)
Introduction Sepsis is a life-threatening condition, especially for patients in the intensive care unit (ICU), where early identification of the prognosis is critical. This study aimed to evaluate the prognostic value of inflammatory markers, clinical scores, and specific laboratory findings for predicting ICU and in-hospital mortality in sepsis patients. Methods A retrospective cohort study was conducted on adult patients with sepsis who were admitted to the ICU of a university hospital between September 2019 and December 2022. To minimize selection bias, all eligible patients during the study period were consecutively included. Data were extracted from electronic medical records and included demographics, clinical characteristics, inflammatory markers, and clinical scores such as the Charlson Comorbidity Index (CCI), Clinical Frailty Scale (CFS), Eastern Cooperative Oncology Group (ECOG) performance status, Simplified Acute Physiology Score 3 (SAPS 3), and Sequential Organ Failure Assessment (SOFA). The primary outcomes were ICU and in-hospital mortality. Univariate and multivariate Cox regression analyses were performed to identify predictors of mortality. Results A total of 213 ICU patients with sepsis were included in the study. The patients were 62.0% male with a mean age of 73.1 ± 12.6 years. The ICU and in-hospital mortality rates were 29.6% and 36.6%, respectively. Non-survivors had higher clinical severity scores and poorer nutritional and perfusion profiles than survivors. Multivariate analysis revealed that elevated lactate levels (a marker of tissue hypoperfusion) and higher SAPS 3 scores were independently associated with ICU mortality. For in-hospital mortality, lower albumin levels and higher SAPS 3 scores were significant predictors. Conclusions High lactate and SAPS 3 scores were independent predictors of mortality, while higher albumin levels showed a potential protective effect. Early identification of these factors may aid in the management of sepsis.